Oral treprostinil is associated with improved survival in FREEDOM-EV and its open-label extension - Grünig, Ekkehard; Rahaghi, Franck; Elwing, Jean; Vizza, Carmine Dario; Pepke-Zaba, Joanna; Shen, Jieyan; Yao, Hua; Hage, Antoine; Rosenkranz, Stephan; Vonk, Madelon; Balasubramanian, Vijay; Yuanhua, Yang; et al. (Advances in therapy, 2024)
In the event-driven FREEDOM-EV trial, oral treprostinil delayed clinical worsening in patients with pulmonary arterial hypertension (PAH). Open-label extension studies offer additional data about tolerability, efficacy, and survival, especially for those initially assigned placebo. The aim of the current study was to determine if oral treprostinil changed survival when considering the parent and extension study, if treprostinil provides functional benefits for participants initially assigned to placebo, and if the benefits observed for those treated with treprostinil were durable.